Distressed setting and profound challenges: Pandemic influenza preparedness plans in the Eastern Mediterranean Region - Mamunur R. Malik; Zaeem Ul Haq; Quaid Saeed; Ruth Riley; Wasiq M. Khan (Elsevier, 2018)
Background: Influenza pandemics are unpredictable and can have severe health and economic implications. Preparedness for pandemic influenza as advised by the World Health Organization (WHO) is key in minimizing the potential impacts. Pandemic Influenza Preparedness (PIP) Framework is a global public-private initiative to strengthen the preparedness. A total of 43 countries receive funds through Partnership Contribution (PC) component of PIP Framework to enhance preparedness; seven of these fall in the WHO's Eastern Mediterranean Region. We report findings of a desk review of preparedness plans of six such countries from the Region. Methods: The assessment was done using a standardized checklist containing five criteria and 68 indicators. The checklist was developed using the latest WHO guidelines, in consultation with influenza experts from the Region. The criteria included preparation, surveillance, prevention and containment, case investigation and treatment, and risk communication. Two evaluators independently examined and scored the plans. Results: Pandemic preparedness plan of only one country scored above 70% on aggregate and above 50% on all individual criteria. Plans from rest of the countries scored below satisfactory on aggregate, as well as on individual preparedness criteria. Among the individual criteria, prevention and containment scored highest while case investigation and treatment, the lowest for majority of the countries. In general, surveillance also scored low while it was absent altogether, in one of the plans. Conclusions: This was a desk review of the plans and not the actual assessment of the influenza preparedness. Moreover, only plans of countries facilitated through funds provided under the PC implementation plan were included. The preparedness scores of majority of reviewed plans were not satisfactory. This warrants a larger study of a representative sample from the Region and also calls for immediate policy action to improve the pandemic influenza preparedness plans and thereby enhance pandemic preparedness in the Region. Keywords: Pandemic influenza, Preparedness plans, Eastern Mediterranean Region